Determining the impact of computer-aided control of educational achievements for the health of students - A.V. Savonova (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The problem of the health of students during the control of knowledge on the example of studying valeological disciplines. In the experiment involved 186 students. Age 17-19 years. The positive effect of regular thematic automated monitoring the health of students. In particular, during unit of knowledge and at exam time. Showed a statistically significant reduction in the average level of reactive anxiety in students of the experimental group, compared to its initial values (before the final test, it fell by 37.91). For comparison, before final testing of the control group, it only reduced by 10.42%. It was determined that a regular automated testing knowledge can be used to organize healthkeeping support professional development of future teachers.